2008
DOI: 10.1590/s1020-49892008001200005
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal violence in three Caribbean countries: Barbados, Jamaica, and Trinidad and Tobago

Abstract: Objectives. This article reports the prevalence of two types of interpersonal violence (IPV) (sexual and physical) and one type of aggression (psychological) in three low-to-middle-income ABSTRACTBased on recent studies of violence and injury reporting high and rising rates of morbidity and mortality as well as high associated economic costs, violence and injury must now be seen as a major public health problem (1-3), especially in the Caribbean (4-6). In addition, there is growing evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 40 publications
3
39
0
1
Order By: Relevance
“…The current IPV was 27 % (Stockman et al 2014). In other Caribbean countries, high rates of physical IPV (45.3–50 %) and sexual IPV (52.8–72.6 %) have been reported (LeFranc et al 2008). A recent analysis of data on IPV from population-based surveys conducted in 12 Latin American and Caribbean countries reported substantial lifetime (13.4–17.2 %) and past year (6.5–12 %) prevalence of physical violence (Bott et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The current IPV was 27 % (Stockman et al 2014). In other Caribbean countries, high rates of physical IPV (45.3–50 %) and sexual IPV (52.8–72.6 %) have been reported (LeFranc et al 2008). A recent analysis of data on IPV from population-based surveys conducted in 12 Latin American and Caribbean countries reported substantial lifetime (13.4–17.2 %) and past year (6.5–12 %) prevalence of physical violence (Bott et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In common with its West Indian neighbours, The Bahamas has not dissociated itself from its violent past. Violence in The Bahamas has continued to increase (United Nations Office on Drugs and Crime & World Bank, 2007), most notably in the increasing number of people who suffer violent deaths each year (Le Franc, Samms-Vaughan, Hambleton, Fox, & Brown, 2008;Hanna, 2011). Even homicide rates in The Bahamas are 6.3 times higher than in the United States of America (United Nations Office on Drugs and Crime, 2013), despite the United States of America being a country which is well-known for gun violence (National Institute of Justice, 2013) and high prison populations driven by violent crime (O'Hear, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, familial victimisation was not related with greater acceptance of physical domestic violence. Although prior research exploring such a relationship is lacking, recent empirical evidence demonstrated low acceptance of wife beating among Caribbean women (Tran et al, 2016), in spite of the frequent occurrence of IPV in the region (Le Franc et al, 2008). One possible explanation of differential associations between child victimisation and attitudes towards domestic violence and violence against girls, is that the process of violence normalisation may apply across settings (i.e., violent treatment first experienced in the family is also accepted in romantic relationships) but not across victim types (i.e., abuse of girls does not expand into accepting marital abuse of women).…”
mentioning
confidence: 99%
“…Support for the supposition that pro-violence attitudes are contingent on context is provided by prior research demonstrating that general interpersonal violence and partner violence do not commonly co-occur (Le Franc et al, 2008) and that not all maritally violent men use violence outside the home (Anderson & Bushman, 2002;Holtzworth-Munroe & Meehan, 2004).…”
mentioning
confidence: 99%